PENGEMBANGAN DIRI GURU UNTUK MENGHADAPI PENDIDIKAN PROFESI GURU (PPG) - Silitonga, R H Yanti; Mataheru, Wilmintjie (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2021)
The community service carried out at SMAN 1 Seram Barat has the aim of preparing teachers to face teacher professional education (PPG) by providing complete information about PPG in the form of lectures and training in portfolio preparation. This activity is to meet the needs of teachers based on the results of interviews, admitting that they lack knowledge about teacher professional education and have difficulty making portfolios. The number of teachers who participated in this activity was 23 people. Based on the results of the questionnaire, it was found that the level of satisfaction in participating in the activities reached 87.83% while the percentage of the level of ease of understanding the material of the activity was 86.52% and the level of usefulness of the material was 89.13%